2019
DOI: 10.1038/s41467-019-08523-4
|View full text |Cite
|
Sign up to set email alerts
|

Clothianidin seed-treatment has no detectable negative impact on honeybee colonies and their pathogens

Abstract: Interactions between multiple stressors have been implicated in elevated honeybee colony losses. Here, we extend our landscape-scale study on the effects of placement at clothianidin seed-treated oilseed rape fields on honeybees with an additional year and new data on honeybee colony development, swarming, mortality, pathogens and immune gene expression. Clothianidin residues in pollen, nectar and honeybees were consistently higher at clothianidin-treated fields, with large differences between fields and years… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
40
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 53 publications
(46 citation statements)
references
References 64 publications
6
40
0
Order By: Relevance
“…Bees encounter pesticides when they contact flower parts to drink nectar and collect floral pollen from flowering crops such as fruit, nut and seed crops. Consuming nectar and pollen exposes them to sublethal concentrations of these compounds that can accumulate in stored foods or in body tissues (Moffat et al, 2016;Osterman et al, 2019) and affect behaviours such as foraging (Henry et al, 2012;Muth and Leonard, 2019;Schneider et al, 2012;Yang et al, 2008), navigation (Fischer et al, 2014) and dance (Eiri and Nieh, 2016). Certain pesticides, such as neonicotinoids, are undetectable by bees when they are found in nectar, and so bees unwittingly consume these substances (Kessler et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Bees encounter pesticides when they contact flower parts to drink nectar and collect floral pollen from flowering crops such as fruit, nut and seed crops. Consuming nectar and pollen exposes them to sublethal concentrations of these compounds that can accumulate in stored foods or in body tissues (Moffat et al, 2016;Osterman et al, 2019) and affect behaviours such as foraging (Henry et al, 2012;Muth and Leonard, 2019;Schneider et al, 2012;Yang et al, 2008), navigation (Fischer et al, 2014) and dance (Eiri and Nieh, 2016). Certain pesticides, such as neonicotinoids, are undetectable by bees when they are found in nectar, and so bees unwittingly consume these substances (Kessler et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have now confirmed that bees exposed to neonicotinoids for long periods at field-realistic concentrations (Dively and Kamel, 2012;Osterman et al, 2019;Rortais et al, 2005;Sanchez-Bayo and Goka, 2014) have difficulty learning to associate floral scent with food (Decourtye et al, 2004;Mengoni Goñalons and Farina, 2015;Tison et al, 2019;Zhang and Nieh, 2015). Most of this research has used simple, Pavlovian conditioning to study how neonicotinoid exposure affects the rate of olfactory learning to a food reward (but see Mengoni Goñalons and Farina, 2015;Zhang and Nieh, 2015;Stanley et al, 2015;.…”
Section: Introductionmentioning
confidence: 99%
“…For example, impaired nest thermoregulation has been found in bumble bees when exposed to imidacloprid [25]. However, the negative effects of neonicotinoids may be dependent on both the compound and the level of exposure seen under field conditions [26,27].…”
Section: Introductionmentioning
confidence: 99%
“…Varying impacts may result from differing landscape composition (Carvalheiro, Seymour, Nicolson, & Veldtman, ; Mallinger et al, ; Park et al, ) or from differences between species in life‐history traits (Tuell, ) or the sensitivity to pesticides (Arena & Sgolastra, ). Honeybees may be less impacted by pesticides than wild bees, as their large colonies can compensate for individual forager losses (Henry et al, ; Osterman et al, ; Rundlöf et al, ). Boosted bee populations in organic farms are not necessarily due to reduced pesticide exposure.…”
Section: Introductionmentioning
confidence: 99%